Analisis Sanksi Tindak Pidana Korupsi dalam Perma Nomor 1 Tahun 2020 Ditinjau dari Konsep Ta’zir dalam Fikih Jinayah - Fadilla, Intan Nur; Santoso , Arif Dian (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2021)
In fiqh jinayah, criminal sanctions for corruptors are included in the ta'zir punishment adjusted to the decision of ulul 'amri based on several considerations because several jarimah are relevant to the concept of corruption, jarimah ghulul and al-rishwah. The Supreme Court formulates sentencing guidelines for judges. It issues them into Supreme Court regulations (PERMA) Number 1 of 2020 to realize legal certainty, justice, and proportional benefits in imposing crimes against perpetrators of criminal acts of corruption. This paper aims to identify and analyze the application of ta’zir in the sentencing guidelines issued by the Supreme Court from the perspective of fiqh jinayah by prioritizing the benefit of the people. The research method used in this study uses normative legal research, and it can be concluded: 1. Criminal sanctions commonly applied by the jarimah ta’zir are imprisonment and a fine formulated in PERMA Number 1 of 2020. 2. The guidelines for punishment in the Supreme Court regulations are by the concept of ta’zir because criminal sanctions are determined proportionally based on several considerations, namely the criteria for the high and low impact of the act and The profit obtained by the perpetrator determines the size of the criminal sanction imposed by the judge.